Conharmonic Curvature Tensor on N(K)-Contact Metric Manifolds. (27th July 2011) - Ghosh, Sujit; De, U. C.; Taleshian, A.
Abstract : The object of the present paper is to characterizeN(k) -contact metric manifolds satisfying certain curvature conditions on the conharmonic curvature tensor. In this paper we study conharmonically symmetric, ξ -conharmonically flat, andϕ -conharmonically flatN(k) -contact metric manifolds.